Proximal influences in two-on-two globins: Effect of the Ala69Ser replacement on Synechocystis sp. PCC 6803 hemoglobin - Knappenberger, Jane A. (2006)
The cyanobacterium Synechocystis sp. PCC 6803 (S6803) expresses a two-on-two globin in which His46 (distal side) and His70 (proximal) function as heme iron axial ligands. His46 can be displaced by O(2), CO, and CN(−), among others, whereas His70 is not labile under native conditions. The residue preceding the proximal histidine has been implicated in controlling globin axial ligand reactivity; the details of the mechanism, however, are not well understood, and little information exists for bis-histidyl hexacoordinate proteins. In many vertebrate hemoglobins and in the Synechocystis protein, the position is occupied by an alanine whereas, in myoglobins, it is a serine involved in an intricate hydrogen bond network. We examined the role of Ala69 in S6803 hemoglobin through the effects of an Ala → Ser replacement. The substitution resulted in minor structural perturbations, but the holoprotein's response to temperature-, urea-, and acid-induced denaturation was measurably affected. Enhanced three-state behavior was manifested in the decoupling of heme binding and secondary structure formation. Urea-gradient gel experiments revealed that the stability of the apoprotein was unchanged by the replacement and that a slight alteration of the folding kinetics occurred in the holoproteins. Cyanide-binding experiments were performed to assess trans effects. The apparent rate constant for association decreased two-fold upon Ala69Ser replacement. This deceleration was attributed to a change in the lifetime of a state containing a decoordinated His46. The results demonstrated that, as in vertebrate globins and leghemoglobin, proximal influences operate to determine fundamental dynamic and thermodynamic properties of the protein.